KEPENTINGAN EKONOMI RUSIA DI ASIA TIMUR: HUBUNGAN EKONOMI DENGAN TIONGKOK - Jamal Din Aulia (UNIDA Gontor, 2022)
Russia is trying to get out of worrying about the world economy amid sanctions imposed by the West and its allies. This concern has implications for efforts to find new economic partners such as China. Historically, bilateral relations between Russia and China have been conflicting due to different interests. However, along with Western sanctions and worsening relations with the West, there is an impetus to strengthen relations between the two countries. Russia views China as an important partner in the economic field. This is based on the influence of China's significant economic power in recent decades. This is evidenced by the existence of various agreements and economic cooperation agreed upon by both parties. In addition, Russia's approach with China can be an opportunity to strengthen its influence in the Asian region, especially its closeness with Japan. This research focuses on Russia's economic interests to be achieved by looking at its closeness with China.